Suppurative keratitis caused by Streptococcus pneumoniae after cataract surgery. Issue 11 (November 1994) - Charteris, D G; Batterbury, M; Armstrong, M; Tullo, A B
Abstract : Six elderly patients are described (age range 76-86 years) in whom a characteristic peripheral suppurative keratitis developed 1-36 months after uncomplicated cataract surgery. A corneal section had been used in all patients and four or five interrupted nylon sutures were present at the time of onset. Streptococcus pneumoniae was cultured from a corneal scrape in all cases. Treatment with appropriate antibiotics resulted in slow resolution though supplementary topical steroids were necessary in five of the six patients, and corneal opacification persists in all cases.